Do Acute Bouts of Resistance Training Influence the Psychometric Status and Affective State of Prepubertal Weightlifters?. (2022) - Hanen, Werfelli; Rebai, Rebai; Hammami, Raouf; Granacher, Urs; Selmi, Walid; Moran, Jason
No abstract available